On transformation formulae for theta hypergeometric functions - Denis, R. Y.; Singh, S. N.; Singh, S. P. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
Using an identity and certain summation formulas for truncated theta hypergeometric series, we establish transformationformulas for finite bilateral theta hypergeometric series.